2008
DOI: 10.1038/nsmb.1535
|View full text |Cite
|
Sign up to set email alerts
|

ATP-dependent unwinding of U4/U6 snRNAs by the Brr2 helicase requires the C terminus of Prp8

Abstract: SummaryThe spliceosome is a highly dynamic machine requiring multiple RNA-dependent ATPases of the DExD/H-box family. A fundamental unanswered question is how their activities are regulated. Brr2 function is necessary for unwinding the U4/U6 duplex, a step essential for catalytic activation of the spliceosome. Here we show that Brr2-dependent dissociation of U4/U6 snRNAs in vitro is activated by a fragment from the C-terminus of the U5 snRNP protein Prp8. In contrast to its helicase-stimulating activity, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
162
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(169 citation statements)
references
References 58 publications
6
162
1
Order By: Relevance
“…It is interesting to compare these findings with two recent studies performed in yeast (Boon, et al, 2007;Maeder, et al, 2009). Both studies showed that the mutations which cause RP in human patients, when present in yeast Prp8 protein, result in its reduced association with the DEAD-box helicase Brr2p in the yeast nucleus (Boon, et al, 2007;Maeder, et al, 2009).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It is interesting to compare these findings with two recent studies performed in yeast (Boon, et al, 2007;Maeder, et al, 2009). Both studies showed that the mutations which cause RP in human patients, when present in yeast Prp8 protein, result in its reduced association with the DEAD-box helicase Brr2p in the yeast nucleus (Boon, et al, 2007;Maeder, et al, 2009).…”
Section: Discussionmentioning
confidence: 74%
“…Both studies showed that the mutations which cause RP in human patients, when present in yeast Prp8 protein, result in its reduced association with the DEAD-box helicase Brr2p in the yeast nucleus (Boon, et al, 2007;Maeder, et al, 2009). The association of Prp8p with Brr2p is thought to be essential for the production of a mature spliceosome and yeast carrying the RP-causing mutations have reduced splicing activity.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 25 DEAD-box proteins in Saccharomyces cerevisiae, five (eIF4A, Fal1, Ded1, Dbp5, and Dbp8) are known to be regulated by cofactors (12,19,21,28,34,35,(65)(66)(67). Similarly, three related SF2-helicases from the DEAH and Ski2-like subfamilies (Prp43, Mtr4, and Brr2) are also regulated by cofactors (22,23,25,(68)(69)(70)(71). These cofactors can increase or decrease the rates of ATP hydrolysis, RNA unwinding, or phosphate or RNA release.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, isolated Brr2 is a comparatively weak helicase, 25,40,41 and its U4/U6 di-snRNA substrate is stabilized by extensive base pairing and bound proteins, [12][13][14]29,42,43 suggesting that the helicase may also depend on specific activation to efficiently unwind the U4/U6 duplex at the right time.…”
Section: Brr2 Requires Tight Regulationmentioning
confidence: 99%
“…This idea is in line with previous proposals of Brr2 functioning as a landing pad for multiple other helicases, which might sequentially interact in similar fashion with the C-terminal cassette. 40,41,52,63,64 Based on the observations that a temperature-sensitive yeast Brr2 variant (E909K), encoded by the slt22-1 allele, is synthetically lethal with mutations in U2 or U6 snRNAs that affect the stability or conformation of U2/U6 helix II, and that the ATPase activity of this variant is no longer stimulated by a U2/ U6 duplex, it was proposed that Brr2 might proofread U2/U6 interactions. 45 Furthermore, different cross-linking profiles of wt Brr2 and a variant exhibiting a residue exchange (G858R) in the NC 5 0 HP/separator loop with U6 snRNA 46 together with the latter variant exhibiting a second step defect and showing synthetic lethality with step 2 mutations in Slu7, Prp18 and Prp16 46,49 suggest that Brr2 participates in a transient opening of the catalytic core between the 2 steps of splicing, which is characterized by the intermittent disruption of U6-5SS and U2-U6 interactions.…”
Section: Brr2 Regulation During Splicingmentioning
confidence: 99%